How Does Public Knowledge, Attitudes, and Behaviors Correlate in Relation to COVID-19? A Community-Based Cross-Sectional Study in Nepal - Hridaya Raj Devkota; Tula Ram Sijali; Ramji Bogati; Andrew Clarke; Pratik Adhikary; Rajendra Karkee (Frontiers Media S.A., 2021)
Background: The COVID-19 pandemic has created a global health emergency requiring an effective public health response including citizen's roles in preventing spread and controlling the pandemic. Little is known about public knowledge, beliefs and behaviors in-relation to the pandemic in Nepal. This study aims to assess knowledge, attitude and practices (KAP) toward COVID-19 among the general public and to identify associated factors.Methods: A cross-sectional survey was conducted between May-June 2020 with a sample of 645, recruited from 26 hospitals across Nepal. We conducted telephone interviews using a semi-structured questionnaire related to KAP regarding COVID-19. T-test and one-way ANOVA was conducted to determine group differences for socio-demographic variables. Linear regression and correlational analysis were performed to identify associated factors and measure strength and direction of relationships.Results: Overall mean scores for knowledge, attitude and practice were 11.6 (SD 4.5), 2.7 (SD 1.8), and 9.9 (SD 1.93) respectively, but differed by socio-demographic characteristics. Positive but weak linear correlations were observed between knowledge-practice (r = 0.19, p < 0.01) and attitude-practice (r = 0.08, p < 0.05). The relationship between knowledge and education was fairly strong (r = 0.34, p < 0.01). Province, place of residence, ecological area, age, gender and caste/ethnicity were also significantly associated with KAP score of participants.Conclusion: The study found varying degrees of correlation between Knowledge, Attitude and Practice that may increase as the pandemic evolves in Nepal. Knowledge and level of education had positive associations with attitude and adherence to precautionary measures. The findings suggest a need for targeted community awareness interventions for the most vulnerable populations, men, those with no school education, the elderly and people living in rural areas.